2017
DOI: 10.1038/ncomms15211
|View full text |Cite
|
Sign up to set email alerts
|

An invariability-area relationship sheds new light on the spatial scaling of ecological stability

Abstract: The spatial scaling of stability is key to understanding ecological sustainability across scales and the sensitivity of ecosystems to habitat destruction. Here we propose the invariability–area relationship (IAR) as a novel approach to investigate the spatial scaling of stability. The shape and slope of IAR are largely determined by patterns of spatial synchrony across scales. When synchrony decays exponentially with distance, IARs exhibit three phases, characterized by steeper increases in invariability at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(125 citation statements)
references
References 53 publications
13
108
0
Order By: Relevance
“…The average temporal correlation of plots of the same functional group (i.e., plots reflecting the same physiological response) is between 0.40 and 0.45 — this shows that their synchrony is far from perfect, and suggests that stochastic effects play an important role in decreasing synchrony. This corresponds well to the concept of decreasing temporal variability with spatial scale (Wang & Loreau, ; Wang et al., ) — the low level of synchrony, even between plots of the same type in close proximity, suggests that we can expect rapid stabilization of fluctuations (i.e., of CV) when we increase the area of sampled plots. Nevertheless, the fact that synchrony is not weaker between blocks than within blocks does not provide strong support for the idea of spatial decay of correlations (Wang & Loreau, ).…”
Section: Discussionsupporting
confidence: 82%
“…The average temporal correlation of plots of the same functional group (i.e., plots reflecting the same physiological response) is between 0.40 and 0.45 — this shows that their synchrony is far from perfect, and suggests that stochastic effects play an important role in decreasing synchrony. This corresponds well to the concept of decreasing temporal variability with spatial scale (Wang & Loreau, ; Wang et al., ) — the low level of synchrony, even between plots of the same type in close proximity, suggests that we can expect rapid stabilization of fluctuations (i.e., of CV) when we increase the area of sampled plots. Nevertheless, the fact that synchrony is not weaker between blocks than within blocks does not provide strong support for the idea of spatial decay of correlations (Wang & Loreau, ).…”
Section: Discussionsupporting
confidence: 82%
“…Low variability can be seen as an indicator of a stable ecosystem. Therefore, to obtain a proper stability measure, we take the reciprocal of variability, which is called invariability (Haegeman et al, ; Wang et al, ), I(A)=1CVt2(P(A))=meant2(P(A))vart(P(A)). …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, temporal variability, defined as the coefficient of variation of total biomass, productivity, or another ecosystem property of interest, can be readily quantified for areas of different size (Wang & Loreau, ). Using invariability, the inverse of variability, as a measure of stability, Wang et al () proposed the invariability–area relationship (IAR) to describe the spatial scaling of ecosystem stability. They showed that, similarly to SARs, empirical IARs have a triphasic shape on a log‐log plot, suggesting a connection between SARs and IARs.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, ecosystem stability increases with spatial scale (Wang & Loreau, ; Wang et al., ). Here, we used:log10false(Sfalse)=c+z×log10false(Afalse)where S , c ′, z ′, and A are the ecosystem stability, intercept, slope, and area, respectively, to illustrate how scaling affects ecosystem stability (Figure a–c).…”
Section: Methodsmentioning
confidence: 99%